PENGARUH SELF EFFICACY TERHADAP HASIL BELAJAR AQIDAH AKHLAK - Septiana Ayunigsih; Ahmad Muslich; Anip Dwi Saputro (TARBAWI:Journal on Islamic Education, 2021)
Self-efficacy is the belief that a person has to do his or her job well. Learning outcomes are the overall abilities obtained after carrying out the learning process at school and are expressed in the form of numbers or test scores. The purpose of the study was to determine the significant effect of selfefficacy on learning outcomes of aqidah morals of fourth grade students at MIT Al-Madinah Balong Ponorogo. MIT Al-Madinah Balong Ponorogo is a madrasa that has been developing since 2012. The learning process of moral aqidah at MIT Al-Madinah has a goal to create a generation that is intelligent, creative, independent and has good morals and science and technology insight. The results showed that the students' self-efficacy results were 64.15% in the medium category and the learning outcomes of aqidah morals were 49.06% in the good category. This research method is quantitative method with ex post facto approach and survey. The population used is all fourth grade students in the 2020/2021 academic year at MIT Al-Madinah Balong Ponorogo totaling 55 students. The sampling technique used is random sampling, which is how to take the entire sample in the population. Data collection techniques with questionnaires, observation and documentation. Meanwhile, to perform data analysis using SPSS version 17.0 program. Based on the results, it was concluded that there was no significant effect of self-efficacy on learning outcomes of aqidah morals for fourth grade students in the 2020/2021 academic year at MIT Al-Madinah Balong Ponorogo.